Faktor Yang Mempengaruhi Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Panambungan Makassar - Fattah, Nurfachanti; Zulfahmidah, Zulfahmidah; Darma, Sidrah; Syahruddin, Febie Irsandy; Bakri, Sri Intan Akmal (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Diarrhea is a bowel disorder characterized by defecation more than 3 times a day with the consistency of liquid stools may be accompanied by blood. The World Health Organization (WHO) in 2017 stated that diarrheal disease is the main cause of child mortality and morbidity in the world. The purpose of this study was to analyze the factors related to the incidence of diarrhea in children under five in the work area of ​​the Panambungan Health Center Makassar City in 2021. Method in this type of research was an analytical observational study with a cross sectional type of research, with a sample size of 91 mothers under five with purposive sampling technique. The results of chi-square analysis were that there was a relationship between the incidence of diarrhea under five and mother's knowledge (p = 0.000), hand washing behavior (p = 0.000) and there was no relationship between the incidence of diarrhea under five and nutritional status (p = 0.174) and water sources net (p=0.269). In conclusion, there is a relationship between the level of mother's knowledge and handwashing behavior with the incidence of diarrhea in toddlers in the working area of ​​the Panambungan Makassar Health Center in 2021.